Million dollar baby - Eastwood, Clint; Haggis, Paul (Lakeshore Entertainment in association with Warner Bros. Pictures, 2004)
Frankie Dunn (Clint Eastwood) is a veteran boxing trainer who has devoted his life to the ring and has precious little to show for it; his daughter never answers his letters, and a fighter he's groomed into contender status has paid him back by signing with another manager, leaving Frankie high and dry. His best friend and faithful employee Eddie Dupris is a former fighter who Frankie trained. In his last fight, Eddie suffered a severe injury, a fact that brings Frankie great guilt. One day, Maggie Fitzgerald (Hilary Swank) enters Frankie's life, as well as his gym, and announces she needs a trainer. Frankie regards her as a dubious prospect, and isn't afraid to tell her why: he doesn't think much of women boxing, she's too old at 31, she lacks experience, and has no technique. However, Maggie sees boxing as the one part of her life that gives her meaning and won't give up easily. Finally won over by her determination, Frankie takes on Maggie, and as she slowly grows into a viable fighter, an emotional bond develops between them. When a tragedy befalls one of the three characters, each comes to a decision that shows how the relationships in the film have changed them. Adapted from a short story by F.X. Toole, a former corner man with years of experience in the fight game, Million Dollar Baby also stars Morgan Freeman, Anthony Mackie, and Mike Colter.